The Mind the search for the mind - Hanser, David; Hemingway, John. (New York WNET, 1988)
What is mindn Is it simply the gray organ nestled inside every human head, or is it something moren This video explores these questions, providing a historical context from ancient Greece through Sigmund Freud's first attempts at psychoanalysis and shedding light on the meaning of the unconcious and concious mind.
VHS
Keywords: Brain; Psychology